Language on the margins: multilinguality, marginality and linguistic precarity in the Nigerian context - Oloruntoba-Oju, Taiwo (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
Multilingualism and multilinguality are conspicuous and sometimes contentious features of the sociolinguistic profile of many African countries. This article looks at the manner in which multilingualism and multilinguality key into marginality and precarity at both societal and individual levels in a representative African community such as Nigeria. Examining the nexus between language, socio-economic status, and government policy, the article suggests that the faulty management of multilingualism in African states produces a precarious multilinguality among citizens across the different social strata. The resultant ‘linguistic precarity’ creates capacity underdevelopment, entrenched poverty and the devaluation of social capital at societal and individual levels. The article draws data from three key sociolinguistic domains in Nigeria – the school, the linguistic landscape of the urban streets, and the political terrain – to illustrate the interesting and theoretically germane ways in which multilinguality, marginality and precarity intersect.